MARKERS OF INFLAMMATION AND ANTIOXIDANT SYSTEM IN THE ORAL FLUID OF 12-YEAR-OLD CHILDREN, DEPENDING ON THE BODY MASS INDEX - Reyzvikh, O.E.; Макаренко, О.А.; Shnaіder S.A.; Babenya, A.A.; Klenovskaya, S.V. (World of Medicine and Biology, 2020)
The results of biochemical studies of the oral fluid in 12 years old children with different body mass index indicate a significant increase in urease activity in children both from the side of hypo- and hypertrophy. This fact indicates a high level of contamination with opportunistic bacteria in the oral cavity in children of the observed groups at the initial stage of the study. The activity of the secretory enzyme lysozyme is reduced in Chernomorsk children with hypotrophy; however, an increase in the activity of lysozyme in the oral fluid, as a rule, indicates the initial stage of the disease, or a period of remission. The high activity of lysozyme can be considered as an adaptive response to the development of pathology. The imbalance of these indicators causes the development of dysbiosis, which leads to pathological changes in the oral cavity. The obtained results indicate the increase of the degree of dysbiosis in the oral cavity in children both in Odesa (1.61 and 1.30) and in the Chernomorsk (3.08 and 4.02). In our opinion, dysbiotic and inflammatory reactions in the oral cavity are protective in relation to the parodont tissues.